Remyelination therapies for multiple sclerosis: optimizing translation from animal models into clinical trials. (3rd August 2021) - Sutiwisesak, Rujapope; Burns, Terry C.; Rodriguez, Moses; Warrington, Arthur E.
ABSTRACT: Introduction: Multiple sclerosis (MS) is the most common inflammatory disease of the central nervous system (CNS). Demyelination, the main pathology in MS, contributes to clinical symptoms and long-term neurological deficits if left untreated. Remyelination, the natural repair of damaged myelin by cells of the oligodendrocyte lineage, occurs in MS, but eventually fails in most patients as they age. Encouraging timely remyelination can restore axon conduction and minimize deficits. Areas covered: We discuss and correlate human MS pathology with animal models, propose methods to deplete resident oligodendrocyte progenitor cells (OPCs) to determine whether mature oligodendrocytes support remyelination, and review remyelinating agents, mechanisms of action, and available clinical trial data. Expert opinion: The heterogeneity of human MS may limit successful translation of many candidate remyelinating agents; some patients lack the biological targets necessary to leverage current approaches. Development of therapeutics for remyelination has concentrated almost exclusively on mobilization of innate OPCs. However, mature oligodendrocytes appear an important contributor to remyelination in humans. Limiting the contribution of OPC mediated repair in models of MS would allow the evaluation of remyelination-promoting agents on mature oligodendrocytes. Among remyelinating reagents reviewed, only rHIgM22 targets both OPCs and mature oligodendrocytes.